Gamification in Higher Education: Enhancing Student Motivation and Cognitive Outcomes Through Game-Based Learning - Andres Villanueva; Dina Destari; Dodi Setiawan Riatmaja (Yayasan Adra Karima Hubbi, 2026)
The increasing demand for active, engaging, and meaningful learning in higher education has encouraged the adoption of innovative instructional strategies such as gamification. Traditional teaching approaches often struggle to sustain student motivation and to promote higher-order cognitive outcomes, particularly in digitally mediated learning environments. This study aims to examine the role of gamification in higher education by analyzing its effectiveness in enhancing student motivation and cognitive outcomes through game-based learning. A quantitative quasi-experimental research design was employed, involving undergraduate students divided into experimental and control groups. Data were collected using validated motivation questionnaires and cognitive achievement tests aligned with course learning objectives, and were analyzed using descriptive and inferential statistical techniques. The results demonstrate that students exposed to gamified learning environments show significantly higher levels of intrinsic motivation, engagement, and persistence compared to those in non-gamified settings. In addition, gamification was found to have a positive and significant effect on cognitive outcomes, particularly in comprehension, application, and problem-solving skills. These findings indicate that gamification contributes not only to affective engagement but also to meaningful cognitive development. In conclusion, the study confirms that well-designed gamification can function as an effective pedagogical approach in higher education, supporting both motivational and cognitive dimensions of learning when aligned with instructional goals.